Co-creative Accompaniment: Building Renewed Relationships through Arts-Based Kinmaking - linares, annais (Critical Studies in Improvisation / Études critiques en improvisation, 2025)
This work delves into the convergence of arts-based community making, social sculpture, and kinship practices within a socially engaged artistic framework. Exploring concepts like accompaniment, Haitian notions of konesans and balans, and examining kinship beyond human connections, I propose arts-based kin making as a collaboratively imagined and enacted set of practices.Drawing inspiration from Project Row Houses, notions of kinship and other scholarly works, this work aims to address both human and species loneliness amid the ecological crisis. Arts-based kin making emerges as a collaborative practice, fostering empathy, connection, and social connection through creative expression. I envision these concepts as intertwined elements guiding my practice toward redefining our relationship with the world.